3D compression algorithms and system-on-chip design for ultrasonic imaging applications - Govindan, Pramod (ProQuest Dissertations & Theses, 2015)
Ultrasonic systems are widely used in imaging applications for nondestructive evaluation, quality assurance and medical diagnosis. These applications require large volumes of data to be processed, stored, and/or transmitted in real-time. Therefore, it is essential to compress the acquired ultrasonic radio frequency (RF) signal without inadvertently degrading desirable signal features. Signal fidelity, computational speed and resource utilization are the major parameters to be considered while designing the architecture for the compression algorithm. In this study, two algorithms for ultrasonic signal compression are analyzed based on: sub-band elimination using discrete wavelet transform; and decimation/interpolation using time-shift property of Fourier transform. Both algorithms offer high signal reconstruction quality with a peak signal-to-noise ratio (PSNR) between 36 dB to 39 dB for minimum 80% compression. The computational loads and signal reconstruction quality are examined in order to determine the best compression method in terms of the choice of DWT kernel, sub-band decomposition architecture and computational efficiency. Furthermore, for compressing a large amount of volumetric information, 3D compression algorithms are designed by utilizing the temporal and spatial correlation properties of the ultrasonic RF signals. The performance analysis indicates that the 3D compression algorithm presented in this study offers an overall 3D compression ratio of 95% with a minimum PSNR of 27 dB. Furthermore, the DWT based ultrasonic 3D data compression algorithm is implemented on a reconfigurable ultrasonic system-on-chip hardware platform targeted for real-time ultrasonic imaging applications. The reconfigurable platform allows analysis of multiple architectures to suit various applications. In this study, hardware and software architectures of the 3D ultrasonic compression algorithm implemented on Xilinx Zynq all programmable system-on-chip platform are discussed, along with the analysis of computational performance. Both implementations provide a high signal compression ratio of about 98% with good quality signal reconstruction. This study demonstrates that, compressing 33 MBytes of experimental ultrasonic 3D data into 0.42 MBytes requires only 84 millisecond for hardware architecture, and one minute for software architecture, making both designs highly suitable for real-time ultrasonic imaging applications. Furthermore, the 3D compression is implemented by using OpenCL, which is adaptable to various platforms such as CPUs, GPUs and FPGAs. Therefore, OpenCL provides similar computational performance as that of hardware architecture, and the same flexibility as that of software implementation. This study demonstrates that the OpenCL implementation of ultrasonic 3D compression algorithm on Nvidia GT 750M graphical processing unit (GPU) completes the operation in less than one second.